2015
DOI: 10.1016/j.engstruct.2014.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moment redistribution and compressive membrane action on punching strength of flat slabs

Abstract: Type of publication:Peer reviewed journal article The punching shear strength of interior column connections of flat slabs has traditionally been investigated with isolated test specimens subjected exclusively to hogging bending moments. However, the behavior of such specimens is different from that of actual flat slabs, as the potentially beneficial phenomena of moment redistribution between hogging and sagging moments and compressive membrane action cannot take place in the conventional experiments. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 15 publications
3
53
0
4
Order By: Relevance
“…8a and b). Modelling the slab only until 0.22L (setup (b) and setup (b) mod ) results in a softer flexural behaviour than the continuous slab; this has already been demonstrated for the case of vertical loads alone [28]. The difference in stiffness between setup (b) and setup (b) mod results from the additional edge reinforcement that is provided in setup (b) mod .…”
Section: Response Comparison Between Setup Configurations and Prototymentioning
confidence: 83%
See 1 more Smart Citation
“…8a and b). Modelling the slab only until 0.22L (setup (b) and setup (b) mod ) results in a softer flexural behaviour than the continuous slab; this has already been demonstrated for the case of vertical loads alone [28]. The difference in stiffness between setup (b) and setup (b) mod results from the additional edge reinforcement that is provided in setup (b) mod .…”
Section: Response Comparison Between Setup Configurations and Prototymentioning
confidence: 83%
“…The influence of the boundary conditions on the deformation capacity of slabcolumn connections has been demonstrated by previous numerical studies, under both vertical load [28] and combined vertical load and transferred moment [29]. It is therefore essential to evaluate the capacity of each setup to reproduce the behaviour of slabcolumn connections of the prototype building.…”
Section: Response Comparison Between Setup Configurations and Prototymentioning
confidence: 99%
“…Only a few analytical models for punching address this effect. 8,11 Compressive membrane action (CMA)…”
Section: Redistribution Between Hogging and Sagging Momentsmentioning
confidence: 99%
“…These specimens model the negative (hogging) moment area around a column, support, or loading point (isolated from the rest of the continuous slab), where the only redistribution possible is that between radial and tangential moments. Although such tests are affordable and relatively easy to perform, results of experiments [2][3][4][5][6][7] and nonlinear analyses [8][9][10] of slabs with rotational and in-plane edge restraints have shown that isolated test specimens may not suitably model the behavior and strength of actual continuous slabs. This is caused by the fact that continuous slabs exhibit two phenomena that cannot appear in isolated specimens, namely redistribution between negative (hogging) and positive (sagging) moments and compressive membrane action (CMA), which may increase the flexural and punching capacity of the slab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation